Polarization Transformation of Electromagnetic Waves on a Reflector Array of Short-Circuited Coaxial-Sector Waveguides - Antonenko, J. V.; Gribovsky, A. V. (Видавничий дім «Академперіодика», 2012)
Polarization characteristics of the reflective two-dimensionally periodic array of short-circuited coaxial-sector waveguides are investigated. Frequency dependences of Stokes parameters of the reflected wave are presented at normal and oblique incidence of a plane linearly polarized electromagnetic wave. Dependences of Stokes parameters on length of the short-circuited coaxialsector waveguides are calculated. Possibility of transformation of the incident linearly polarized wave into the reflected wave with circular polarization of the right or left rotation of electric field vector is shown, both at normal, and at oblique incidence of plane wave.